Doing business with Russia : a guide to investment opportunities and business practice - Terterov, Marat (Global market briefings., 2005)
"Now in its 4th edition, Doing Business with Russia is the most authoritative guide available to trade and investment opportunities, the structural, legal and market changes underway in the country and the mechanics of business engagement there."--Jacket